Description of Dioszegia patagonica sp. nov., a novel carotenogenic yeast isolated from cold environments - Trochine, Andrea; Turchetti, Benedetta; Vaz, Aline B. M.; Brandao, Luciana; Rosa, Luiz H.; Buzzini, Pietro; Rosa, Carlos; Libkind, Diego (International Journal of Systematic and Evolutionary Microbiology)
During a survey of carotenogenic yeasts from cold and oligotrophic environments in Patagonia, several yeasts of the genus Dioszegia (Tremellales, Agaricomycotina) were detected, including three strains that could not be assigned to any known taxa. Analyses of internal transcribed spacer and D1/D2 regions of the large subunit rRNA gene showed these strains are conspecific with several other strains found in the Italian Alps and in Antarctica soil. Phylogenetic analyses showed that 19 of these strains represent a novel yeast species of the genus Dioszegia . The name Dioszegia patagonica sp. nov. is proposed to accommodate these strains and CRUB 1147 T (UFMG 195 T =CBMAI 1564 T =DBVPG 10618 T =CBS 14901 T MycoBank MB 819782) was designated as the type strain. This Dioszegia species accumulates biotechnologically valuable compounds such as carotenoid pigments and mycosporines. Fil: Trochine, Andrea. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto Andino Patagónico de Tecnologías Biológicas y Geoambientales. Universidad Nacional del Comahue. Instituto Andino Patagónico de Tecnologías Biológicas y Geoambientales.; Argentina Fil: Turchetti, Benedetta. Università Degli Studi Di Perugia; Fil: Vaz, Aline B. M. Universidade Federal Do Minas Gerais. Instituto de Cs.biologicas; Brasil Fil: Brandao, Luciana. Universidade Federal Do Minas Gerais. Instituto de Cs.biologicas; Brasil Fil: Rosa, Luiz H. Universidade Federal Do Minas Gerais. Instituto de Cs.biologicas; Brasil Fil: Buzzini, Pietro. Università Degli Studi Di Perugia; Fil: Rosa, Carlos. Universidade Federal do Minas Gerais; Brasil Fil: Libkind, Diego. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto Andino Patagónico de Tecnologías Biológicas y Geoambientales. Universidad Nacional del Comahue. Instituto Andino Patagónico de Tecnologías Biológicas y Geoambientales.; Argentina